2000
DOI: 10.1177/152660280000700403
|View full text |Cite
|
Sign up to set email alerts
|

Transrenal Fixation of Aortic Endografts: Intermediate Follow-up of a Single-Center Experience

Abstract: In the intermediate period, transrenal fixation appears to have no adverse effects on renal blood flow. Moreover, in patients with no evidence of renal disease or preoperative RAS < 60%, it does not precipitate or cause progression of renal stenosis. However, patients with preoperatively documented RAS > or = 60% are a concern and mandate further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…patients with AAA and earlier studies support the renal safety of suprarenal stent graft fixation. [6][7][8][9][10][11][12][21][22][23][24] However, long-term effect of deployed uncovered stent on the renal artery ostia remains a major concern. This is especially apparent in patients with concomitant renal artery atherosclerotic disease because it is characterised by a natural history of progression to total occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…patients with AAA and earlier studies support the renal safety of suprarenal stent graft fixation. [6][7][8][9][10][11][12][21][22][23][24] However, long-term effect of deployed uncovered stent on the renal artery ostia remains a major concern. This is especially apparent in patients with concomitant renal artery atherosclerotic disease because it is characterised by a natural history of progression to total occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Marin et al 31 compared 37 patients treated with suprarenal stent-grafts and 16 receiving infrarenal devices; at a mean 10-month follow-up, there was no difference in serum creatinine levels between the groups. Lobato et al 21 reported no persistent increase in creatinine levels after 35 EVRs with suprarenal endografts. Bove et al 9 followed 28 patients treated with a suprarenal stent-graft for 6 months; of the 19 patients with normal preoperative renal function, 3 (15.8%) had a persistent elevation in serum creatinine.…”
Section: Discussionmentioning
confidence: 97%
“…The effectiveness and safety of EVAR has been debatable in AAA patients with conical neck, because making a reliable seal was difficult to achieve. Conical neck had the risk of postprocedural complications due to the difficulty of proximal stent graft fixation and seal in some papers [6,7,9,10]. On the contrary, the length, angle and size rather than the shape of the neck had been introduced as risk factors for type Ia endoleak in other papers [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…EVAR with non-IFU has been related with increased technical failure [2], type Ia endoleak [3,4] and secondary intervention [2,5]. As one of the hostile neck anatomy, conical neck is difficult to be sealed by the stent graft from aneurysmal sac and it is considered as a contraindication to EVAR in some reports [69]. Conical neck increased the risk of postprocedural complications such as proximal endoleak and stent graft migration [6,7,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation